Lower limb muscle injuries: The good, the bad and the ugly. Issue 104 (July 2018) - Vidoni, Alessandro; Gillett, Mark; Botchu, Rajesh; James, Steven
Highlights: MRI assess severity of muscle injuries. Specific imaging features estimate the return to play time. Three clinico-radiological categories guide rehabilitation. Abstract: Injuries to the lower limb muscles are a common cause of absence from training and competition in athletes. The different muscular groups of the thigh and leg are involved in various activities with kicking and sprinting being responsible for the largest number of injuries. The muscle acts on bone through the tendon and the fascia. The failure of one or more of these structures results in various degrees of loss of function of the muscle(s) involved. Usually, the point of weakness is the interface between different structures with different elastic properties (myofascial, myotendinous, avulsion). Diagnostic imaging is best performed by MRI that provides valuable information about the severity of the injury and its anatomical extent. In this article, we will review the MRI features of muscle injuries which can be used to guide return to play. We will emphasize the clinical implications of the MRI findings by dividing the muscle injuries into three categories "The Good, The Bad and The Ugly" to help the clinician in the planning of the most appropriate rehabilitation strategy.